Recurrent Tolosa–Hunt syndrome - Thu, Phyo-Wai (Tzu Chi Med J, 2020)
The Tolosa–Hunt syndrome (THS) is caused by granulomatous inflammation in the cavernous sinus, superior orbital fissure, or orbit characterized by painful ophthalmoplegia. Here, we report a case of recurrent THS in a 48-year-old female, who initially showed a poor response to low-dose steroids. Each episode involved different cranial nerves and painful ophthalmoplegia. Neuroimaging showed enhancement in the right cavernous sinus. The patient was treated with glucocorticoid pulse therapy and azathioprine. THS was previously considered to be responsive to glucocorticoids. This report demonstrates a case of THS with poor response to steroids and unique presentation of frequent recurrence with different cranial nerve involvement.